2015
DOI: 10.3390/plants4020298
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Regulation and Expression Profiles of Wheat Genes Involved during Phytic Acid Biosynthesis Pathway

Abstract: Phytic acid (PA) biosynthesis pathway genes were reported from multiple crop species. PA accumulation was enhanced during grain filling and at that time, hormones like Abscisic acid (ABA) and Gibberellic acid (GA3) interplay to control the process of seed development. Regulation of wheat PA pathway genes has not yet been reported in seeds. In an attempt to find the clues for the regulation by hormones, the promoter region of wheat PA pathway genes was analyzed for the presence of cis-elements. Multiple cis-ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…The third gene, HORVU1Hr1G048400 , encodes methyltransferase-like protein 17 (mitochondrial), which is known to be drought-responsive proteins involved in reactive oxygen species (ROS) scavenging, cell structure, and cycle, and increased response to drought tolerance [ 41 ]. HORVU1Hr1G050760 encoding Inositol-tetrakisphosphate 1-kinase 1 belongs to the ITPK proteins that have been identified as the intermediate precursor of phytic acid PA biosynthesis [ 42 , 43 ]. During germination, PA is catabolized by phytase enzymes, allowing the remobilization of the sequestered minerals to support juvenile seedling growth [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The third gene, HORVU1Hr1G048400 , encodes methyltransferase-like protein 17 (mitochondrial), which is known to be drought-responsive proteins involved in reactive oxygen species (ROS) scavenging, cell structure, and cycle, and increased response to drought tolerance [ 41 ]. HORVU1Hr1G050760 encoding Inositol-tetrakisphosphate 1-kinase 1 belongs to the ITPK proteins that have been identified as the intermediate precursor of phytic acid PA biosynthesis [ 42 , 43 ]. During germination, PA is catabolized by phytase enzymes, allowing the remobilization of the sequestered minerals to support juvenile seedling growth [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of phytic acid content is a major goal of plant-breeding programs that aim to improve the nutritional quality of crops. Efforts to breed low-phytic-acid (lpa) crops have focused on the genes involved in IP metabolism and compartmentation [ 17 21 ], while the regulatory pathways for IP synthesis and accumulation have received scant attention [ 22 , 23 ]. Moreover, although high IP6 content in seeds was thought to be unnecessary for plant development [ 24 ], many lpa mutants showed a lethal phenotype [ 25 ] or recessionary agronomic traits [ 26 ], including reduced yield and reduced resistance to stress.…”
Section: Introductionmentioning
confidence: 99%
“…myo-Inositol is an important biomolecule in plant metabolism, forming conjugates with plant hormones and acting as a substrate for phosphate accumulation, while isomeric inositols and their O-methyl esters participate in seed desiccation and salt tolerance [32]. Regulation of InsP synthesis by ABA signaling is supported by a report by Aggarwal et al [33], who showed that ABA controls the expression of PA synthesis genes. There is growing evidence for the involvement of plant ITPKs in abiotic stress signaling.…”
Section: Introductionmentioning
confidence: 91%
“…An important role for inositol phosphate kinases during abiotic stress signaling is supported by the regulation of their expression by ABA [33], a potent abiotic stress signaling hormone. It is possible that enzymes from the initial phase of InsP synthesis might also participate in responses to abiotic stress.…”
Section: Transcription Profiling Of Itpk Genes Under Salinity Stressmentioning
confidence: 99%